Management of birth asphyxia at home and health center - Anna Alisjahbana; Sjarif Hidayat; Mintardaningsih Mintardaningsih; Aris Primadi; Enny Harliany; Yulia Sofiatin; Attie Triyanti (Paediatrica Indonesiana, 1999)
Birth asphyxia is the main cause of death in newborns and is an emetgency situation that need immediate action. In Indonesia more than 60% of deliveries are attended by traditional birth attendants. Although infant mortality has decline significantly in the last decade, the neonatal component of IMR however remain the same. The ddinition of birth asphyxia recommended by World Health Organization is: A newborn infant who does not cry and who does not breath or has poor breathing efforts soon after birth. The paper present the result of a fieldstudy conducted in Tanjungsari (West java). The study is part of a multicountry study conducted in four countries organized by World Health Organization. TBAs were trained in the basic steps of resuscitation starting from drying, stimulation, suction and providing. Positive PressureVentilation using a tube and mask device on infants with birth asphyxia Community midwives were trained in the same procedure and additional training for cardiac massage. Team work between TBA and CM was stressed. More infants with birth asphyxia survive, one fr sh Still borninfant survive after vigorous resuscitation. Although the result looks promising, close supervision and regular refreshing courses are necessary to have a significant impact on neonatal mortality.